A fault location method for hybrid transmission lines based on empirical Fourier decomposition - Caixia Tao; Baosheng Xing; Taiguo Li (Archives of Electrical Engineering, 2023)
This paper aims to address the problems of inaccurate location and large computation in hybrid transmission line traveling wave detection methods. In this paper, a new fault location method based on empirical Fourier decomposition (EFD) and the Teager energy operator (TEO) is proposed. Firstly, the combination of EFD and the TEO is used to detect the time difference between the arrival of the initial traveling wave of the fault at the two measurement ends of the hybrid line. Then, when the fault occurs at the midpoint of each line segment and at the connection point of the hybrid line, the time difference between the arrival of the fault traveling wave at the two measurement ends of the line is calculated according to the line parameters. By comparing the obtained time differences, it is determined whether the fault occurs in the first or second half of the line. Finally, the fault distance is calculated using the double-ended traveling wave method according to the fault section. The model was built on PSCAD and the proposed algorithm was simulated on MATLAB platform. The results demonstrate that the proposed method achieves an average fault location accuracy of 98.88% by adjusting transition resistances and fault distances and comparing with other location methods. After validation, the proposed method for locating faults has a high level of accuracy in location, computational efficiency, and reliability. It can accurately identify fault segments and locations in hybrid transmission line systems.